Financial education for female foreign domestic workers in Singapore. (October 2020) - Barua, Rashmi; Shastry, Gauri Kartini; Yang, Dean
Abstract: We evaluate a randomized field experiment to study the effect of financial workshops for domestic workers in Singapore. Groups of women met monthly with a trained mentor. Take-up rates were low and our results are inconclusive as to whether invitations to these workshops improved financial knowledge and behavior. Unexpectedly, treatment assignment had a significant, negative effect on self-reported savings. Further exploration suggests that assignment to treatment could affect participants' awareness of accumulated savings. We find a reduction in the number of savings accounts reported and an increase in the probability respondents report having disagreements with family members over finances.